1996
DOI: 10.1097/00002060-199611000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Thermal Responses to Head and Neck Cooling in Men and Women1

Abstract: Personal cooling systems are used to alleviate symptoms of multiple sclerosis and to prevent increased core temperature during daily activities. The objective of this study was to determine the operating characteristics and the physiologic changes produced by short term use of one commercially available thermal control system. A Life Support Systems, Inc. Mark VII portable cooling system and a liquid cooling helmet were used to cool the head and neck regions of 12 female and 12 male subjects (25-55 yr) in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Hyperthermia decreases seizure threshold acutely (7), while cortical cooling alters brain electrical behavior leading to increased seizure threshold (8-10, 15, 17, 18) and may acutely stop seizures in animal models and patients (7)(8)(9)(10). Cold saline application stops ongoing after-discharges induced by electrical stimulation, and spontaneous interictal epileptiform discharges (19), and stimulation-evoked seizures (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperthermia decreases seizure threshold acutely (7), while cortical cooling alters brain electrical behavior leading to increased seizure threshold (8-10, 15, 17, 18) and may acutely stop seizures in animal models and patients (7)(8)(9)(10). Cold saline application stops ongoing after-discharges induced by electrical stimulation, and spontaneous interictal epileptiform discharges (19), and stimulation-evoked seizures (13).…”
Section: Discussionmentioning
confidence: 99%
“…Shivering was prevented by keeping the torso warm during cooling (13). Cooling efficacy may depend on headgear fit and amount of hair; a 35-year-old man with very short hair whose cooling helmet fit exceptionally well had the lowest IT after 30 min of cooling and the second lowest after 60 min of cooling; head shaving may be beneficial (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anecdotal reports from many patients with MS suggest that sensitivity to heat is one of the primary barriers to performing daily activities and participating in exercise and/or rehabilitation, and this sensitivity can lead physicians to advise patients to avoid exercise because metabolic heat production can increase core temperature and thus exacerbate symptoms 3 . In turn, this lower level of physical activity can lead to a further loss of fitness, muscle tone, and most importantly, a decrease in function and quality of life 7,8 . A…”
mentioning
confidence: 99%
“…fitting garment around the head, torso, or the whole body, with a network of tubing that fits tightly against the skin and cooling through conduction of cold water 7,8,11,12 . Schwid et al 12 found that cooling the head and torso for 1 or 30 days resulted in a small but significant increase in ambulatory function measured by the 25 foot walk test, and visual function improved as measured by Snellen charts.…”
mentioning
confidence: 99%